Selectionbreeding index of sow reproductive quality (bisrq) as – effective method for assessment and selecting high-productive - Khalak, V.; Халак, В. І.; Horchanok, Anna; Horchanok, A.; Horchanok, A. V.; Горчанок, Анна Володимирівна; Lytvyschenko, L.; Litvischenko, L. O.; Litvischenko, Lіudmyla; Lytvyschenko, L. O.; Lytvyshchenko, L.; Литвищенко, Людмила Олександрівна; et al. (Дніпровський ДАЕУ, 2020)
In the article the results of researches the sow reproductive qualities of Large White pigs taking into account their inbreeding differentiation according to the selection breeding index of sow reproductive qualities (BISRQ) are presented.It was established that sows of class M+ exceeded significantly peers of the opposite class Min prolificacy by 3.4 heads, in milk yield by 18,3 kg, in weight of the nest at breaking at the age of 28-35 days by 19,7 kg. The maximum increase in additional products (13,01 %) was obtained from one sow of class M+ and its cost is 320,57 hryvnias.The number of significant correlation coefficients between absolute and integrated indicators of reproductive qualities is 80,0 %; they are positive and vary from +0,331 to + 0,986±0,0027. The correlation coefficient between the uniformity index of a sow’s nest in live weight of piglets at birth (IUN) and the breeding index of sow reproductive quality (BISRQ) is + 0,897±0,0185. The criterion for the selection of highly productive animals according to the breeding index of sow reproductive qualities (BISRQ) is an indicator of 96,22-118,92 points. The use of animals with the indicators of BISRQ provides additional products at the level of 13,01 %. В статті наведені результати досліджень відтворювальних якостей і економічної ефективності використання свиноматок великої білої породи з урахуванням їх внутрішньопородної диференціації по селекційному індексу відтворювальних якостей (СІВЯС). Встановлено, що свиноматки класу М + достовірно перевершували ровесниць протилежного класу М - по багатоплідності на 3,4 гол, молочності - 18,3 кг, масі гнізда при відлученні у віці 28-35 днів - 19,7 кг. Максимальна надбавка додаткової продукції (13,01 %) отримана від однієї свиноматки класу М+ , а її вартість становить 320,57 гривень. Кількість достовірних коефіцієнтів кореляції між абсолютними і інтегрованими показниками відтворювальних якостей становить 80,0%, вони позитивні і змінюються в межах від +0,331 до + 0,986±0,0027. Коефіцієнт кореляції між індексом вирівняності гнізда свиноматки за живою масою поросят при народженні (ІВГ) і селекційним індексом відтворювальних якостей свиноматки (СІВЯС) дорівнює + 0,897± 0,0185. Критерієм відбору високопродуктивних тварин по селекційному індексу відтворювальних якостей свиноматки (СІВЯС) є показник 96,22-118,92 бала. Використання тварин з даними показниками індексу СІВЯС забезпечує отримання додаткової продукції на рівні 13,01%.
Селекційний індекс відтворювальних якостей свиноматки (сівяс) – ефективний метод відбору високопродуктивних тварин
Горчанок Анна Володимирівна https://orcid.org/0000-0003-0103-1477 Литвищенко Людмила Олександрівна http://orcid.org/0000-0002-4239-5405
Keywords: integrated indicators; інтегровані показники; sow; свиноматка; reproductive qualities; відтворювальні якості; economic efficiency; економічна ефективність